Improvement of financial and economic activity of commercial banks by implementing financial technologies ("Journal "U". Economy. Management. Finance.", 2019)
This article discusses the phenomenon of digital evolution of banking industry institutions, which leads to a change in all processes and professional transformation of personnel directly working in the industry under study. The authors note that the introduction and use of financial technology based on big data is becoming one of the main parts of the workflow of commercial banks. It is predicted that in the era of new financial technologies, digitalization of the profession, as an accountant, auditor and controller, may disappear. Control, audit and operational management in a couple of decades will be carried out using artificial intelligence.
Keywords: commercial banks; financial technologies; digital technologies